Computer aided assessments and programming exercises with JACK - Michael Goedicke; Michael Striewe; Moritz Balz (Universität Duisburg-Essen, Institut für Informatik und Wirtschaftsinformatik (ICB), 2008)
In this report a system for computer aided assessments and exercises on Java programming is presented and discussed. The report includes a detailed system description, experiences and evaluations from using the system, plans for future development and a brief overview about related work and discussions.
Keywords: 650; Softwareentwicklung; Programmiersprache; Lehrmaterial